High Temperature Symmetry Non-Restoration And Inverse Symmetry Breaking in the Z2×Z2 Model - Phat, Tran Huu; Hoa, Le Viet; Anh, Nguyen Tuan; Long, Nguyen Van (Communications in Physics, 2008)
The patterns of high temperature symmetry non-restoration (SNR) and inverse symmetry braking (ISB) in the Z2×Z2model are investigated in detail for a specified parameters